Pengaruh Sikap, Norma Subjektif, dan Kontrol Keprilakuan Terhadap Minat Investasi di Crypto Pada Gen Z Kota Palembang - Angellyn Leovia; Fernanda Pricilia; Marcella Angelita (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to determine the influence of attitudes, subjective norms, and behavioral control on investment interest in Crypto on Gen Z in Palembang City. The first type of data used by researchers in this study is primary data. The subjects of this study are Gen Z in Palembang City. Purposive sampling technique is used to take samples of selected Gen Z.